Salvage Radical Prostatectomy for Radio-Recurrent Prostate Cancer: An Updated Systematic Review of Oncologic, Histopathologic and Functional Outcomes and Predictors of Good Response - Grubmüller, Bernhard; Jahrreiss, Victoria; Brönimann, Stephan; Quhal, Fahad; Mori, Keiichiro; Heidenreich, Axel; Briganti, Alberto; Tilki, Derya; Shariat, Shahrokh F (Current oncology (Toronto, Ont.), 2021)
A valid treatment option for recurrence after definite radiotherapy (RT) for localized prostate cancer (PC) is salvage radical prostatectomy (SRP). However, data on SRP are scarce, possibly resulting in an underutilization. A systematic review was performed using MEDLINE (Pubmed), Embase, and Web of Science databases including studies published between January 1980 and April 2020. Overall, 23 English language articles including a total number of 2323 patients were selected according to PRISMA criteria. The overall median follow-up was 37.5 months (IQR 35.5-52.5). Biochemical-recurrence (BCR)-free probability ranged from 34% to 83% at five years, respectively, and from 31% to 37% at 10 years. Cancer specific survival (CSS) and overall survival (OS) ranged from 88.7% to 98% and 64% to 95% at five years and from 72% to 83% and 65% to 72% at 10 years, respectively. Positive surgical margins ranged from 14% to 45.8% and pathologic organ-confined disease was reported from 20% to 57%. The rate of pathologic > T2-disease ranged from 37% to 80% and pN1 disease differed between 0% to 78.4%. Pre-SRP PSA, pre-SRP Gleason Score (GS), pathologic stage after SRP, and pathologic lymph node involvement seemed to be the strongest prognostic factors for good outcomes. SRP provides accurate histopathological and functional outcomes, as well as durable cancer control. Careful patient counseling in a shared decision-making process is recommended.
Keywords: Prostatic Neoplasms; Neoplasm Recurrence, Local; primary radiotherapy; prostatektomie; záchranná terapie; lidé; recurrence; mužské pohlaví; prostate cancer; Male; salvage radical prostatectomy; Salvage Therapy; Treatment Outcome; nádory prostaty; výsledek terapie; lokální recidiva nádoru; Prostatectomy; Humans